2018
DOI: 10.1021/acs.organomet.8b00351
|View full text |Cite
|
Sign up to set email alerts
|

Bench-Stable Nickel Precatalysts with Heck-type Activation

Abstract: Herein, we report the synthesis and characterization of a new class of air- and moisture-stable phosphine-containing nickel(II) precatalysts, which activate through a Heck-type mechanism. The activities of the precatalysts are demonstrated with a carbonyl–ene coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Active nickel(0) species A was generated after reduction of actual catalyst NiCl 2 (PCy 3 ) 2 with trialkylaluminium and attacked the pre-activated silicon center of chlorosilane as nucleophile to furnish cationic Jamison and co-workers developed an air and moisture stable phosphine containing nickel(II) precatalyst featuring alkene-functionalized aryl ligands which activated via Heck-type conditions. [40] Authors shaped nickel(II) pre-catalyst in such a way where associated alkene chain was included in aryl ring. The nickel(II)-pre-catalyst was activated further with the help of triflate reagent.…”
Section: Intermolecular Heck Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active nickel(0) species A was generated after reduction of actual catalyst NiCl 2 (PCy 3 ) 2 with trialkylaluminium and attacked the pre-activated silicon center of chlorosilane as nucleophile to furnish cationic Jamison and co-workers developed an air and moisture stable phosphine containing nickel(II) precatalyst featuring alkene-functionalized aryl ligands which activated via Heck-type conditions. [40] Authors shaped nickel(II) pre-catalyst in such a way where associated alkene chain was included in aryl ring. The nickel(II)-pre-catalyst was activated further with the help of triflate reagent.…”
Section: Intermolecular Heck Reactionsmentioning
confidence: 99%
“…Jamison and co‐workers developed an air and moisture stable phosphine containing nickel(II) pre‐catalyst featuring alkene‐functionalized aryl ligands which activated via Heck‐type conditions [40] . Authors shaped nickel(II) pre‐catalyst in such a way where associated alkene chain was included in aryl ring.…”
Section: Intermolecular Heck Reactionsmentioning
confidence: 99%
“…7 As opposite to Pd(0) and Pt(0), where dicoordinate complexes with phosphine and N-heterocyclic carbene (NHC) ligands are common, L2Ni(0) complexes were isolated exclusively with bulky NHC substituents, even though the phosphine analogs are commonly postulated active species in Ni(0)-Ni(II) catalytic cycles. 8,9 (NHC)2Ni(0) derivatives proved to be proficient precatalysts in a number of bond-forming transformations, 10 and their stoichiometric chemistry targeted mostly the related oxidative addition reactions leading to Ni(I) and Ni(II) complexes. 11 While L2Pt(0) moieties have been shown to act as lone pair donors in a variety of complexes, 12 there is no record of the lighter Ni congeners being able to emulate this binding mode.…”
mentioning
confidence: 99%
“…Synthesis of T-shaped Ni(0) complex 4. (11), Ni1-C 1.902(7), 1.884 (7), Ge1-Cl 2.340(2), 2.3363(18), Ni1···H 2.47(4), C1-Ni1-C19 167.2(3), C-Ni1-Ge1 92.96 (19), 97.26 (19), Cl1-Ge1-Cl2 94.69(4), Ge1-Ni1···H 172.8 (9).…”
mentioning
confidence: 99%
“…31 This complex was not purified, but immediately treated with trimethylsilyl triflate (TMS-OTf), upon which a methallyl nickel triflate complex was rapidly formed. 32 The structure of this complex (P1) was unambiguously characterized using X-ray diffraction ( Figure 2). Under optimized reaction conditions, this precatalyst (P1) facilitated the C-N coupling reaction and provided the desired product in 98% yield in 2 h. Analysis of the crude reaction mixture (GC/MS) showed that N-methallyl aniline was formed during the reaction, consistent with activation of P1 through outersphere nucleophilic attack by aniline at the methallyl ligand.…”
Section: Resultsmentioning
confidence: 99%